Postnatal development and egg morphometry of different breeds of pigeon available at northern Barind tract in Bangladesh - Parvez, Md Najmul Hassan; Islam, Md Reazul; Sarder, Md Jalal Uddin; Gofur, Md Royhan (Asian Journal of Medical and Biological Research, 2020)
Pigeon farming, like chicken and duck farming, is getting popularity nowadays in Bangladesh. The present study was conducted on the postnatal development and morphometry of egg of different breeds of pigeon available at northern Barind tract of Bangladesh. The study was conducted at thirty selected pigeon farms of three districts (Rajshahi, Natore and Pabna) of northern Barind tract of Bangladesh. The postnatal development (weight gain of squabs) of five groups (D0, D7, D14, D21, D28; D=day), and morphometry of eggs (egg weight, egg width (short axis), and length (long axis)) of breeds of pigeon (n=20, each breed) available at northern Barind tract in Bangladesh were collected and analyses with Duncan's Multiple Range test (DMRT). Considerable differences in the postnatal weight gain and egg morphometry were found among breeds of pigeon. The mature body weight of Giribaz, Kormona, Nun and Owl breeds of pigeon were below 300 gm; Satinette, Mookee, Suachandan, Lakkha, Jacobin, Bokhara, Shirajee, Homer and Pouter were 300-500 gm, and King and Strasser were below 800 gm. The postnatal weight of an age group was significantly different (p<0.05) from other age groups of all studied breeds. The highest egg length was 4.37±0.02 cm in Strasser, and the lowest was 3.68±0.01 cm in Giribaz pigeon. The highest egg width was 3.24±0.19 cm in Mookee, and the lowest was 2.73±0.02 cm in Giribug pigeon. The highest egg weight was 21.20±0.49 gm in Strasser, and the lowest was 14.00±0.23 gm in Owl pigeon. Moreover, a relationship between the body weight and egg length, width and weight of pigeons was observed in pigeons of all studied breeds. Asian J. Med. Biol. Res. September 2020, 6(3): 594-598